Citations to highly-cited researchers by leading Universities in Sri Lanka: scientometric analysis - Maheswaran, R.; Perachiselvi, U.; Abbas, L.M.; Balasubramani, R. (University of Jaffna, 2022)
The contributions of leading two Universities of a country to the scholarly literature are higher than that of other universities. Identifying the research output of the lead ing Universities would value their level of contributions. The study aims to trace the research output of two leading Universities in Sri Lanka from 2001 to 2021, as reflected in the Web of Science database. The study has selected the Science Citation Index (SCI) of Web of Science for selecting two leading Sri Lanka universities in terms of total publications in the last two decades (2001–2021). The University of Peradeniya, and the University of Colombo, were identified as leading Universities. The study identified the most prolific authors, collaborating countries, collaborating institutions and the impact of their output in terms of citations per paper (CPP) and relative citation impact (RCI). For visualizing purposes, VOSviewer was used. The study also identified frequently used keywords and channels used for communicating research results. The authors retrieved 7091 documents consisting of journal articles, review papers and proceeding papers. The consistent growth of science research output has been observed. TheUniversity of Peradeniya has more publications than the University of Colombo. An author from the University of Peradeniya published a research paper entitled “Global and regional mortality from 235 causes of death for 20 age groups in 1990 and 2010: a systematic analysis for the Global Burden of Disease Study 2010”, received the highest citations of 7304 among the Sri Lanka leading universities. The study reflects that multi-authored papers have more re search impact in terms of citation received. Australia, USA and England are the most collaborative countries. These two leading Universities in Sri Lanka have a major collaboration with Anna University, the Indian Institute of Technology, Centre for Scientific and Industrial Research (CSIR) of India. The findings can be utilized to suggest certain science research topics that require further focus.
Keywords: Research output; Science Citation Index; Citation; Relative citation impact